PEMECAHAN DORMANSI DAN PERKECAMBAHAN ASAM KURANJI (Dialium indum L.) SECARA MEKANIS DAN KIMIAWI Breaking Dormancy and Seeds Germination of Asam Kuranji (Dialium indum L.) with Mechanical and Chemical - Bakti Nur Ismuhajaroh (Jurnal Hutan Tropis, 2014)
The purpose of the study was to find out the dormancy breaking and the seed germination of Asam kuranji (Dialium indum L.) mechanically by sandpapering the seeds and chemically by immersing them in sulfuric acid (H2SO4). The experiment was conducted at the Plant Physiology Laboratory of Agricultural Faculty of Lambung Mangkurat University from June - August 2013 using Completely Randomized Design (CRD) with 2 x 4 factorial. The first factor was the mechanical treatment  (s0 = without sandpaper and s1 = with sandpaper), the second factor was the chemical treatment (a0 = without immersion, a1 = 70% of H2SO4, a2 = 80% of H2SO4, and a3 = 90% of H2SO4. The data were analyzed by ANOVA at the level of 95% followed by Tukey's test at the level test of 95%. The results showed that the treatments of sandpapering and immersing the seeds significantly affected the % of germination, the length of radicle and the length of hypocotyl. The interaction between treatments of sandpapering and immersion indicated that the higher the concentration of H2SO4 immersion the higher the % of germination, the length of radicle and the length of hypocotyl.Keywords: germination, Dialium indum L., sandpaper, concentration, H2SO4